2020
DOI: 10.1177/0020764020926551
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural study of attitudes toward suicide among young people in India, Italy and Australia

Abstract: Background: An understanding of the cultural aspects of suicidal behavior is essential for the development of culturally appropriate suicide prevention and intervention strategies. Aims: This study explored the attitudes toward youth suicide in 686 Italian, Indian and Australian undergraduate students (18–24 years old). Method: A 21-item suicide attitude inventory titled Attitude towards Youth Suicide (AtYS) scale, included in this paper, was used in the three samples. Results: Four factors were extracted, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Since 2018, we found six additional studies (including two that were previously unavailable), all of which support findings presented in this review. A quantitative study using a new scale found 18-24 year-old Indians' attitudes to suicide as negative, and that they felt suicide could not be prevented and that there were no risk signs [94]. Two other studies found poor levels of knowledge, with one study showing that 53.7% of students had poor knowledge regarding preventive measures of suicidal behaviour [95] and another showing that 43% of school students had inadequate knowledge of substance use [96].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Since 2018, we found six additional studies (including two that were previously unavailable), all of which support findings presented in this review. A quantitative study using a new scale found 18-24 year-old Indians' attitudes to suicide as negative, and that they felt suicide could not be prevented and that there were no risk signs [94]. Two other studies found poor levels of knowledge, with one study showing that 53.7% of students had poor knowledge regarding preventive measures of suicidal behaviour [95] and another showing that 43% of school students had inadequate knowledge of substance use [96].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our results support limited translation of these results to diverse populations. It is well documented that these communities experience (i) social and cultural stigma surrounding suicidal thoughts, behaviors, and associated death [56,57] and (ii) vastly different face-to-face interactions with the healthcare system [58]. For these reasons, our findings may not translate across diverse communities that disproportionately experience these thoughts and behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…Our results support limited translation of these results to diverse populations. It is well documented that these communities experience (i) social and cultural stigma surrounding suicidal thoughts, behaviors, and associated death 54, 55 and (ii) vastly different face-to-face interactions with the healthcare system. 56 For these reasons, our findings may not translate across diverse communities that disproportionately experience these thoughts and behaviors.…”
Section: Discussionmentioning
confidence: 99%